New Distributional Records and Notes on the Pale-bellied White-eye Zostaops consobrinorum - James C Wardill (KUKILA, 2003)
This paper summarizes and reviews our knowledge of the Pale-bellied White-eye Zosterops consobrinorum of south-east Sulawesi, Indonesia. Fieldwork during late 1995 resulted in the discovery of seven new localities for the species on the Sulawesi mainland. In addition we discovered an undescribed race of Z. consobrinorum on Buton Island. These records significantly increase the known distribution of the species. Information on the species' habitat, behaviour, plumage, vocalisations, taxonomy and status is presented and it is concluded that the species is not threatened.